Cash Management in the Revenue Treasury of the Directorate General of State Assets - Rizky Cahyo Wibowo; Dodik Siswantoro (Fakultas Ekonomi dan Bisnis Universitas Udayana, 2025)
Cash management within the Revenue Treasurer of the Directorate General of State Assets (DJKN) remains a recurring issue identified by the Audit Board of Indonesia (BPK) in its 2024 audit. This study aims to identify the root causes of suboptimal cash management practices in the Revenue Treasurer and propose recommendations for improvement. This research adopts a case study approach using qualitative methods. Data were collected through document reviews and in-depth interviews with key stakeholders. The analysis was conducted within the framework of Governance, Risk Management, and Compliance (GRC), with research stages following the Soft Systems Methodology (SSM). The findings identify three primary root causes: weaknesses in governance processes and structures, limitations in human resource capabilities, and inefficiencies in the utilization of technology and information systems.Based on these findings, this study recommends that DJKN strengthen stakeholder engagement and oversight, enhance the competency of personnel involved in cash management, and further develop and optimize the use of technology and information systems for managing non-tax revenue cash flows within the Revenue Treasurer.